A catalogue of the Heteroptera (Hemiptera) or true bugs of Argentina - Coscarón, María Del Carmen (Zootaxa, 2017)
The Heteroptera (Hemiptera) of Argentina are catalogued. A total of 686 genera and 2030 species are listed together with their synonyms. References are given to the original descriptions and the subsequent taxonomic position, and the geographic distribution is included.